Pengaruh Perbedaan Persentase Pemberian Pakan Alami Cacing Sutera (Tubifex sp) dan Pakan Buatan terhadap Pertumbuhan Berat Mutlak Benih Ikan Patin (Pangasius hypophthalmus) - Rizaldi Wibowo Aji; Sumaryam Sumaryam; Didik Budiyanto (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The objective of this study was to determine the effect of different percentages of natural feed (Tubifex sp.) and artificial feed on the absolute weight gain of striped catfish (Pangasius hypophthalmus) fry. The study was conducted at PBIAT Muntilan for 30 days using an experimental method. A Completely Randomized Design (CRD) was applied with five treatments and five replicates. The treatments were as follows: A (100% pellet), B (75% pellet + 25% Tubifex sp.), C (50% pellet + 50% Tubifex sp.), D (25% pellet + 75% Tubifex sp.), and E (100% Tubifex sp.). ANOVA analysis showed that different proportions of natural feed (Tubifex sp.) and artificial feed significantly affected absolute weight gain. The most optimal feeding ratio for enhancing the absolute weight gain of striped catfish fry was found in treatment E, where 100% Tubifex sp. was provided, resulting in the highest absolute weight gain of 4.876 grams. Water Quality Parameters: During the study, the recorded water temperature ranged from 25.1 to 25.4ºC, pH ranged from 6.7 to 6.8, and dissolved oxygen ranged from 6.6 to 6.7 ppm. ANOVA analysis of these three water quality parameters showed no significant differences among treatments. However, the temperature was below the optimal range for the growth of striped catfish (Pangasius hypophthalmus) fry.